Film Cerdas Ramah Lingkungan dari Eceng Gondok dan Bunga Tapak Dara Sebagai Indikator Kesegaran Udang - Syamsuri, M. Mahfudz Fauzi; Agathis, Sefina; Agustin, Tasya; Sefriany, Mega Retha; Dzahabiyyah, Dafinah; Sholehah, Isma Rohatis; Fatmasari, Desy; Nurwidiyani, Ria; Triawan, Deni Agus (Food Scientia: Journal of Food Science and Technology, 2025)
An effort to address food waste, a global issue, is the labeling of food products. Current expiry labeling on food products is often ineffective as it provides insufficient information to consumers regarding product quality. This research aims to innovate bioplastic film into a smart label to solve this problem. Consumers can simply observe the label’s color change as an indicator of food freshness. This smart film was fabricated by using melt intercalation method, involving the mixing of water hyacinth fiber, corn starch, and glycerin into water, followed by addition of periwinkle flower powder. The smart film exhibits acidity sensitivity, indicated by a significant color change from red ( in acidic conditions) to yellow ( in alkaline conditions). Test on shrimp freshness by using the smart film showed a color shift from white to greenish-yellow. Mechanical property testing revealed that the smart film has a tensile strength of 19.62 MPa and elongation of 8%, fulfilling the biodegradable plastic criteria based on SNI 7818:2014. Therefore, this eco-friendly smart film could be utilized as an indicator shrimp freshness.